FRI0018 The ability of disease activity measures to predict major therapeutic change in us veterans with rheumatoid arthritis. (12th June 2018) - Cannon, G.; Teng, C.-C.; Accortt, N.A.; Collier, D.H.; Lin, T.-C.; Sauer, B.C.
Abstract : Background: Current rheumatoid arthritis (RA) treatment guidelines recommend the use of disease activity measures (DAMs) to guide RA therapy. These guidelines recommend considering escalation of therapy in RA patients with high or moderate disease activity. Recent work by our group has demonstrated that many RA patients with high/moderate RA by Disease Activity Score with 28 joints (DAS28) did not have therapy escalated despite active disease (DAS28 ≥3.2). Objectives: 1) To determine if the rate of major therapeutic change (MTC) for RA patients with high/moderate disease activity based on DAS28 was similar when measured using two other common DAMs; 2) to compare the ability of different DAMs to predict MTC across the full spectrum of RA disease activity. Methods: US Veterans enrolled in the VA Rheumatoid Arthritis (VARA) registry with 1) a complete set of DAMs (DAS28, Clinical Disease Activity Index [CDAI], Routine Assessment of Patient Index Data 3 [RAPID3]) recorded (index date), 2) two other visits during the preceding 18 months separated by at least 60 days, and 3) clinical data available for 18 months prior to through 30 days following index date were eligible. Each patient was assessed for MTC within 1 week before and 30 days after index date. MTC was defined as any of the following: 1) initiation of new biologic or nonbiologic DMARD, 2) escalation of DMARD dose by ≥25%, 3) initiation of prednisone (as new agent or after 90 day gap during baseline), or 4) increase in monthly average prednisone dose by 25% and/or 5) injection of 2 or more joints with corticosteroids. MTC was analysed by DAM severity thresholds of 1) high, moderate, low, and remission, and 2) high, high/moderate, and high/moderate/low levels. Analyses of the latter thresholds included sensitivity, specificity, predictive values, and accuracy estimations for MTC at each DAM level. Results: Of 1776 eligible patients, 89% were male, mean age was 63.4 years, mean disease duration was 13.4 years, 79% tested positive for rheumatoid factor, and 63% positive for anti-cyclic citrullinated peptide antibodies. Overall, 33.1% (591/1776) of patients had an MTC. A markedly larger percentage of patients with high disease activity had MTC (range 55.1%–43.5%) compared to patients with moderate disease (range 38.7%–27.8%) (table 1). Sensitivity, specificity, predictive values, and accuracy at each DAM threshold level varied markedly by DAM, with RAPID3 having a higher sensitivity, lower specificity, and less accuracy than DAS28 or CDAI (table 2). Conclusions: Most patients with high/moderate disease activity did not have a MTC. This observation was consistent regardless of which DAM was utilised. MTC increased with disease activity with all DAMs; however, DAS28 and CDAI appeared to have greater accuracy than RAPID3 at predicting MTC at all disease severity thresholds. There is need for continued evaluation of DAM thresholds for defining disease activity for MTC decisions, better DAMs, and/or better application of DAMs in clinical practice to improve the treatment of patients with active RA. Acknowledgements: This study was sponsored by Immunex, a subsidiary of Amgen. Medical writing assistance provided by Amgen. Disclosure of Interest: G. Cannon Grant/research support from: Amgen, C.-C. Teng Grant/research support from: Amgen, N. Accortt Shareholder of: Amgen, Employee of: Amgen, D. Collier Shareholder of: Amgen, Employee of: Amgen, T.-C. Lin Shareholder of: Amgen, Employee of: Amgen, B. Sauer Grant/research support from: Amgen Inc.